ANALYSIS OF THE DETERMINING FACTORS OF SMILE AESTHETICS (STUDIES ON STUDENTS OF THE ISLAMIC UNIVERSITY OF SULTAN AGUNG SEMARANG) - Elhakamy, Nurul Azkia; Noviyanti, Shella Indri; Praptiningsih, Rahmawati Sri (Jurnal Medali, 2024)
Background: A smile is one of the main components of the attractiveness of a person’s face. Several things build an aesthetic smile. The aesthetic assessment of a smile is a subjective matter, so each individual has their assessment. The purpose of this study was to determine the student’s assessment of the four components of a smile. Method: The research design used in this study was an observational study with a cross-sectional approach with a total of 100 research subjects, which included diploma, bachelor, professional education, master, and postgraduate students. Result: The result obtained from this study showed different results between male and female students. Conclusion: The high smile line was considered by male and female respondents to be aesthetic, and the medium smile line was considered unaesthetic by male respondents and aesthetically for women. The low smile line was considered unaesthetic by both of them. In the smile arc, the parallel smile arc is regarded as an aesthetic smile by both male and female respondents, while the straight smile arc is assessed as an unaesthetic smile by male and female respondents. For male respondents, a smile with a reverse smile arc was assessed as a very unaesthetic smile, while female respondents rated this smile as unaesthetic. In the upper lip curvature aspect, male respondents rated a smile with an upward upper lip curvature as very aesthetic, while female respondents rated it as aesthetic. Both male and female respondents rated Straight upper lip curvature as an aesthetic smile. A smile with downward upper lip curvature is rated as very unaesthetic by male respondents and unaesthetic by female respondents. In the buccal corridor aspect, male and female respondents rated a smile with a narrow and medium buccal corridor as an aesthetic smile. A smile with a wide buccal corridor was rated as very unaesthetic by male respondents, while female respondents rated this smile as unaesthetic.